2022
DOI: 10.3390/ijms23147544
|View full text |Cite
|
Sign up to set email alerts
|

A Non-Cell-Autonomous Mode of DNA Damage Response in Soma of Caenorhabditis elegans

Abstract: Life has evolved a mechanism called DNA damage response (DDR) to sense, signal and remove/repair DNA damage, and its deficiency and dysfunction usually lead to genomic instability and development of cancer. The signaling mode of the DDR has been believed to be of cell-autonomy. However, the paradigm is being shifted with in-depth research into model organism Caenorhabditis elegans. Here, we mainly investigate the effect of DDR activation on the radiosensitivity of vulva of C. elegans, and first found that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…B cells, crucial components of the adaptive immune response, exhibited the highest UPR across all tumors, possibly due to their inherent high antibody demand in response to the cancer cells (Downs-Canner et al , 2022). Unexpectedly, we found that immune cells, traditionally associated with immune surveillance and response, showed high levels of DDR, indicating a potential cell-non-autonomous role for the DDR (Dai et al , 2022). The OSR was found to be high in CAFs across all tumor types, emphasizing a potential role for the OSR in the fibroblasts.…”
Section: Discussionmentioning
confidence: 88%
“…B cells, crucial components of the adaptive immune response, exhibited the highest UPR across all tumors, possibly due to their inherent high antibody demand in response to the cancer cells (Downs-Canner et al , 2022). Unexpectedly, we found that immune cells, traditionally associated with immune surveillance and response, showed high levels of DDR, indicating a potential cell-non-autonomous role for the DDR (Dai et al , 2022). The OSR was found to be high in CAFs across all tumor types, emphasizing a potential role for the OSR in the fibroblasts.…”
Section: Discussionmentioning
confidence: 88%